Stay or Flee? Probability Versus Severity of Punishment in Hit-And-Run Accidents - Stefano Castriota; Mirco Tonin (Center for Economic Studies and ifo Institute (CESifo), 2019)
The empirical literature testing the economic theory of crime has extensively studied the relative importance of the probability and the severity of punishment with reference to planned criminal activities. There are, however, also unplanned crimes and in this paper we focus on a very serious and widespread one, hit-and-run road accidents. In fact, it is not only unplanned, but also largely committed by citizens without criminal records and the decision whether to stay or run must be taken within a few seconds. Using Italian data for the period 1996-2016, we rely on daylight as an exogenous source of variation affecting the probability of apprehension and find that the likelihood of hit-and-run conditional on an accident taking place increases by around 20% with darkness. Relying on two legislative reforms which increased the penalties in case of hit-and-run, we find no significant effect on drivers' behavior. Our results show that criminal activities in unplanned circumstances and under intense time pressure and emotional distress are deterred more by the certainty rather than the severity of legal sanctions.
Keywords: D91; K14; K42; R41; 330; crime; hit-and-run; road; accidents; punishment